Year-round genetic monitoring of mixed-stock fishery of Atlantic cod (Gadus morhua); implications for management. (6th May 2022) - Christensen, Helle Torp; Rigét, Frank; Retzel, Anja; Nielsen, Erik Haar; Nielsen, Einar Eg; Hedeholm, Rasmus Berg
Abstract: Mixed-stock fisheries pose a challenge for fisheries management recommendations and management, as mixed stocks can lead to unintentional over- or under-exploitation of stocks, with both short- and long-term biological and economic consequences. This study demonstrates practical application and implementation of year-round high-resolution genetic stock monitoring in management of mixed Atlantic cod ( Gadus morhua ) stocks in western Greenland. Using a panel of 96 high resolution gene-associated SNPs, we identified the stock of origin for four cod stocks in the two major inshore mixed-stock fisheries. Contribution of individual stocks was quantified to identify if fjord sections, times of year, and fish size, would allow a "clean fishery" with a minimal contribution of the depleted West Greenland Offshore (WGO) population. High level of mixing was identified with 50% of inshore catches originating from the inshore stock, 20% from the East Greenland/Iceland offshore stock, and 30% from the WGO stock. Although some spatiotemporal variation of stock proportions was identified, a practice allowing exclusively fishing a specific stock was not possible. Accordingly, we demonstrate the need to allocate catches at the biological stock level and show that application of high-resolution genetics is a reliable and necessary tool.